Understanding the implications of service contracting in product-service businesses - Phumbua, Sarocha; Tjahjono, Benny (The Operational Research Society, 2012)
Service contracting has been adopted in several industries especially for high value assets with long life time. Such a contract typically specifies asset usage information, availability or capability of the contracted assets required by customers, and the scope of services the manufacturers are obliged to support the assets. Consequently, such a contract imposes major risks to the manufacturers. This paper aims to explore approaches that be used to assist manufacturers to model service contracts in order to understand the risk and reward prior to committing a contract with customer. The work described in the paper involves the development of a simulation model from a case of the ship building industry. The use of the model in aiding contracting decisions is demonstrated through three experiments conducted at the case company. The outcomes have demonstrated the potential of the approaches in practice and contributed to the Product-Service Systems modelling paradigm.
Keywords: Service contract; Product-Service Systems; Simulation